Evaluasi Kualitas Visual Lanskap di Pantai Jimbaran, Kabupaten Badung, Bali - Simanjuntak, Nadia Y Abigail; Semarajaya, Cokorda Gede Alit; Yusiana, Lury Sevita (Jurnal Arsitektur Lansekap, 2023)
Evaluation of Visual Quality of Tourist Landscape in Jimbaran Beach, Badung Regency . Jimbaran Beach as one of the tourist attractions in Badung Regency, Bali does not yet have an optimal arrangement of the constituent elements of the landscape. This affects the visual comfort of its users. So it is important to improve the visual beauty of jimbaran beach tourist attraction. Based on this, this study aims to assess the visual quality of the Jimbaran beach landscape and provide recommendations for structuring the constituent elements of the landscape. The Method used in this research is mix-method which are qualitative by analyzing based on the existing situation and standard from related teories and quantitative to find out the visual quality of landscape elements by a method called Scenic Beauty Estimation (SBE). The results of the overall assessment by respondents showed that the visual quality of Jimbaran beach was included in the moderate category. Recommendations for landscape arrangements are needed based on the high visual quality of jimbaran beach landscape. The recommendation is expected to be an input for managers to improve the visual quality of the Jimbaran beach landscape.